Prognostic and predictive factors in patients treated with chemotherapy for advanced urothelial cancer: where do we stand?. (January 2015) - Buti, Sebastiano; Ciccarese, Chiara; Zanoni, Daniele; Santoni, Matteo; Modena, Alessandra; Maines, Francesca; Gilli, Annalisa; Bria, Emilio; Brunelli, Matteo; Rimanti, Anita; Cascinu, Stefano; Ardizzoni, Andrea; et al.
ABSTRACT : The standard of care for patients with local advanced or metastatic urothelial carcinoma is chemotherapy. However, results with this are rather disappointing, and validated prognostic factors and biomarkers of tumor response, which are useful in the decision-making process, are still lacking. PubMed databases were searched for articles published until November 2013. Several promising clinical and biological candidate prognostic factors or markers of tumor response to first- or second-line therapy, such as hemoglobin, performance status, visceral metastasis and ERCC1, hENT1 and EMT markers, have been identified and described in this article. In summary, clinical parameters and molecular profiling could revolutionize the management of local advanced or metastatic urothelial cancer, but an improvement in individualized therapeutic approaches still seems distant.